(untitled) (Journal of actual problems of jurisprudence, 2023)
Occupying the 9th place in the world in terms of the size of its territory, the Republic of Kazakhstan, due to its geographical location, local climate, dependence on transboundary water resources and other reasons, belongs to the category of one of the poorly supplied regions of the globe. This fact entails the need to organize the processes of the most careful attitude to water resources, legal support for its rational use and all-round protection from pollution, clogging and depletion, in order to ensure water security not only for citizens of the Republic of Kazakhstan, but for all mankind. In the system of water management activities of Kazakhstan, a significant place is given to transboundary water resources, since more than half of its renewable water resources are formed outside its territorial boundaries. Moreover, Kazakhstan is located at the ends of transboundary rivers and cannot fully control the flow of water into its territory from upstream neighbors. This problem becomes the reason for the growth of political and socio-economic tension between the countries in whose territory transboundary water resources are localized. As a rule, these processes are accompanied by the emergence of contradictions and conflicts, both at the local and interstate levels. The correct definition of the concept and legal status of transboundary water resources of the Republic of Kazakhstan is the starting point for achieving significant goals and results in the full implementation of the state water policy in the field of use and protection of the water fund, water supply and sanitation. Key words: water legal relations, water legislation, protection of the water fund, system of water relations, transboundary water resources.